Optimal Regimens and Clinical Breakpoint of Avilamycin Against Clostridium perfringens in Swine Based on PK-PD Study - Huang, Anxiong; Luo, Xun; Xu, Zihui; Huang, Lingli; Wang, Xu; Xie, Shuyu; Pan, Yuanhu; Fang, Shiwei; Liu, Zhenli; Yuan, Zonghui; Hao, Haihong (Frontiers in Pharmacology, 2022)
Clostridium perfringens (Cp) leads to significant morbidity and mortality in swine worldwide. Avilamycin showed no cross resistance and good activity for treatment of Cp. The aim of this study was to formulate the optimal regimens of avilamycin treatment Cp infection based on the clinical breakpoint (CBP). The wild-type cutoff value (COWT) was defined as 0.25 μg/mL, which was developed based on the minimum inhibitory concentration (MIC) distributions of 120 Cp isolates and calculated using ECOFFinder. Pharmacokinetic - pharmacodynamics (PK-PD) of avilamycin in ileal content were analyzed based on high-performance liquid chromatography (HPLC) method and Winnolin software to set up the target of PK-PD index (AUC0-24h/MIC)ex based on sigmoid Emax modeling. The PK parameters of AUC0-24h, Cmax, and Tmax in intestinal tract were 428.62 ± 14.23 hμg/mL, 146.30 ± 13.41 μg/mL and 4 h, respectively. The target of (AUC0-24h/MIC)ex for bactericidal activity in intestinal content were 36.15 h. The PK-PD cutoff value (COPD) was defined as 8 μg/mL and calculated by Monte Carlo simulation. The dose regiment designed from PK-PD study was 5.2 mg/kg mixed feeding and administrated for treatment Cp infection. Five respectively strains with different MICs were selected as the infection pathogens, and the clinical cutoff value (COCL) was defined as 0.125 μg/mL based on the relationship between MIC and possibility of cure (POC) following the Nonlinear Regression Analysis (NRA), CART and “Window” approach. The CBP was set to be 0.25 μg/mL and selected by the integrated decision tree recommended by CLSI. The formulation of optimal regimens and clinical breakpoint is good for clinical treatment and control the drug resistance.